2012
DOI: 10.1007/s10493-012-9645-7
|View full text |Cite
|
Sign up to set email alerts
|

The invasive spider mite Tetranychus evansi (Acari: Tetranychidae) alters community composition and host-plant use of native relatives

Abstract: The tomato spider mite Tetranychus evansi Baker and Pritchard (Acari: Tetranychidae), is a worldwide pest of solanaceous crops that has recently invaded many parts of the world. In the present study we examined the ecological impact of its arrival in the Mediterranean region. The spider mite and phytoseiid mite assemblages in various crop and non-crop plants in three areas of Valencia (Spain) were studied a few months before and 10 years after the invasion of T. evansi. According to rarefaction analyses, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 47 publications
8
56
0
Order By: Relevance
“…It could be that these species rarely encounter each other in the field. However, field data show that this is not the case (Ferragut et al 2013). Still, given that invasion of Europe by T. evansi is recent (Boubou et al 2012), it may be that contact has not occurred for sufficient time for adaptation to the presence of the competitor to occur.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It could be that these species rarely encounter each other in the field. However, field data show that this is not the case (Ferragut et al 2013). Still, given that invasion of Europe by T. evansi is recent (Boubou et al 2012), it may be that contact has not occurred for sufficient time for adaptation to the presence of the competitor to occur.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a recent T. evansi expansion has led to new distribution overlaps, mainly in Europe (Boubou et al 2012). In the field, they are frequently found on the same plant (Ferragut et al 2013). First-male sperm precedence has been found in T. urticae, although dependent on the mating interval (Boudreaux 1963;Helle 1967): a second mating occurring within 24 h after the first can still produce some offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, T. evansi was found to outcompete T. urticae (Sarmento et al, 2011b). Moreover, field observations in Spain showed that T. evansi invasion replaced native Tetranychus species including T. urticae (Ferragut et al, 2013). Hence, given that T. evansi suppresses tomato plant defence, the question arises how T. evansi prevents T. urticae to profit from this.…”
Section: Discussionmentioning
confidence: 99%
“…This species is characterized by a high reproductive capacity and a gregarious behavior compared to T. urticae (Azand em e- Hounmalon et al, 2014). Besides its invasive nature, recent reports have indicated that T. evansi has replaced native spider mite species, hence presenting new pest management challenges (Ferragut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%